2015
DOI: 10.2147/ndt.s89417
|View full text |Cite
|
Sign up to set email alerts
|

Addiction profile in probation practices in Turkey: 5-year data analysis

Abstract: IntroductionWhile drug addiction is a global problem, it is important for every region to know the general features of its own addicts in order to develop effective treatment programs. This study presents sociodemographic data of the individuals diagnosed with drug addiction.MethodsIn this study, data of the patients between the years of 2009 and 2014 were retrospectively analyzed. The patients were assessed at psychiatry polyclinics according to probation practices of drug abuse. The study involved 513 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
1
2
1
1
Order By: Relevance
“…In the present research, craving is shown to be one of the important factors affecting the treatment process under probation. While there exist previous studies which demonstrate the effect of the existence of treatment attempts about addiction problems on compliance to treatment under probation [24], no important effect of previous treatment attempts was found in this study. This may be the result of the low average number of previous treatments in our sample.…”
Section: Resultscontrasting
confidence: 91%
“…In the present research, craving is shown to be one of the important factors affecting the treatment process under probation. While there exist previous studies which demonstrate the effect of the existence of treatment attempts about addiction problems on compliance to treatment under probation [24], no important effect of previous treatment attempts was found in this study. This may be the result of the low average number of previous treatments in our sample.…”
Section: Resultscontrasting
confidence: 91%
“…For this reason, the results, such as that substance users fall behind regarding education, working life and income compared with healthy volunteers, could be related to addiction. This is compatible with data from similar studies [1,34].…”
Section: Discussionsupporting
confidence: 93%
“…Substance use disorders cause serious psychological, medical, social and economic problems [1]. It has been reported that approximately 5.5% of the world's adult population-in other words, 271 million people between the ages of 15 and 64-used at least one drug in 2017, and in the same year, the number of people with substance use disorders increased to 35 million.…”
Section: Introductionmentioning
confidence: 99%
“…SCs are widely used in Turkey and around the world in recent years. They have hundreds of chemical types and these are usually called K2, Spice, Bonzai, Jamaika, and so forth [ 1 ] It has both similar and different pharmacokinetic and pharmacodynamic mechanisms with major active component of marijuana (Δ(9)-tetrahydrocannabinol-THC) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%